Remediation of domestic and industrial effluents using algae - Nene, S. N.; Gera, G.; Yewalkar, S. N. (Algal Biorefinery: An Integrated Approach, 2016)
In the environment, microbial activity is considered as one of the most important mechanisms for the abatement of water-borne pollutants. In the natural and anthropogenic environment the wide range of contaminates are not eliminated by single specie but by the complex interaction of a mixed microbial population performing complementary reactions. This principle is very much applicable for the treatment of the industrial and domestic wastewater, which has excess of nitrogenous compounds (N) and phosphates (P). N and P along with various organic pollutants, if not properly treated, would create a devastating impact on natural aquatic ecosystems. Among the many other disturbing impacts, most prevalent is the phenomenon of eutrophication, which is the accumulation of high levels of organic matter and the decomposing organisms, which deplete the oxygen in water, and causing the death of other organisms, such as fish. The excess nutrients in the aquatic ecosystem support the growth of various phytoplanktons. It not only spoils the water quality but also adversely affects the whole aquatic ecosystem. This chapter will address the possibility of effectively utilizing a natural microbial flora/consortium, enriched with the rapidly growing algae for the remediation of polluted water bodies.